Coherent many-body exciton in van der Waals antiferromagnet NiPS3 - Kang, Soonmin; Kim, Kangwon; Kim, Beom Hyun; Kim, Jonghyeon; Sim, Kyung Ik; Lee, Jae-Ung; Lee, Sungmin; Park, Kisoo; Yun, Seokhwan; Kim, Taehun; Nag, Abhishek; Walters, Andrew; et al. (Nature (London), 2020)
An exciton is the bosonic quasiparticle of electron–hole pairs bound by the Coulomb interaction 1 . Bose–Einstein condensation of this exciton state has long been the subject of speculation in various model systems 2 , 3 , and examples have been found more recently in optical lattices and two-dimensional materials 4 – 9 . Unlike these conventional excitons formed from extended Bloch states 4 – 9 , excitonic bound states from intrinsically many-body localized states are rare. Here we show that a spin–orbit-entangled exciton state appears below the Néel temperature of 150 kelvin in NiPS 3 , an antiferromagnetic van der Waals material. It arises intrinsically from the archetypal many-body states of the Zhang–Rice singlet 10 , 11 , and reaches a coherent state assisted by the antiferromagnetic order. Using configuration-interaction theory, we determine the origin of the coherent excitonic excitation to be a transition from a Zhang–Rice triplet to a Zhang–Rice singlet. We combine three spectroscopic tools—resonant inelastic X-ray scattering, photoluminescence and optical absorption—to characterize the exciton and to demonstrate an extremely narrow excitonic linewidth below 50 kelvin. The discovery of the spin–orbit-entangled exciton in antiferromagnetic NiPS 3 introduces van der Waals magnets as a platform to study coherent many-body excitons. A spin–orbit-entangled exciton state in the van der Waals material NiPS 3 is observed, and found to arise from many-body states of a Zhang–Rice singlet.